Detection of methionine 1-linked ubiquitin chains in intestinal inflammation and cancer models - Luukkonen, Veera (My University, 2023)
Ubiquitination is a post-translational modification, which involves the attachment of polyubiquitin chains to substrate proteins. Methionine 1-linked ubiquitin (Met1-Ub) chains have an important role in nuclear factor-κB transcription factor activation in immunity and inflammation. To study Met1-ubiquitination in intestinal inflammation and carcinogenesis, this study aimed to produce a Met1-Ub antibody and a GST-tagged Met1-Ub-specific ubiquitin binder (Met1-SUB) and to apply them for Met1-Ub detection in Western blot, immunocytochemistry, and immunohistochemistry. Met1-Ub antibody and GST-Met1-SUB were produced recombinantly in mammalian and bacterial expression systems, respectively. Their function and specificity were tested in Western blot with cancer cells and mouse colon tissue. The antibody was used in immunocytochemistry to stain and quantify Met1-Ub expression in cancer cells, and optimized for immunohistochemistry staining to study Met1-ubiquitination in the colon of keratin 8 knockout (K8-/-) mice, a chronic colitis model. The antibody specifically recognized changes in Met1-Ub expression in cell and tissue lysates after immunoprecipitation with Met1-SUB. The antibody detected significant differences in Met1-ubiquitination upon overexpression or inhibition of Met1-Ub chains in immunocytochemistry. It was found that Met1-Ub chains localize in the cytoplasm of cancer cells and in the intestinal epithelial cells of mouse colon. However, immunohistochemistry staining could not detect changes in Met1-Ub expression in wildtype and K8-/- mice colon. This study provides versatile tools for Met1-Ub detection that can be optimized for other applications and model systems. In the future, these tools could potentially be used to study Met1-ubiquitination in patient samples and aid in the discovery of new biomarkers for inflammatory bowel disease and colorectal cancer diagnostics.
Keywords: Met1-linked ubiquitin, inflammation, antibody, ubiquitin binder, Western blot, immunocytochemistry, immunohistochemistry, inflammatory bowel disease, cancer